Clinical violence in nursing students - Aghajanloo, Ali (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND: One of the significant issues in health studies is violence. Although violence against nurses has been recognized as a major occupational problem, its magnitude and extent is not clearly defined. The aim of this study was to determine the extent and types of violence during clinical training of nursing students. METHODS: In this descriptive and cross-sectional study, 180 sophomores, juniors and seniors of Shahid Beheshti, Tehran and Iran Medical Universities were selected by quota sampling method. A questionnaire was used for collecting data regarding violence over the past year. Content and test-retest methods were used for evaluating its validity and reliability, respectively. RESULTS: Findings showed that 6.7%, 8.3% and 39.4% of the students experienced physical assault, physical menace and insult, respectively, over the past year. Most cases of the assaults (66.7%) were done by patients, most menaces by staff as well as patients’ attendants (18.1%) and most insults by staff (33.7%) and patients (31%). No significant relation was found between the sex as well as the educational year of the students and the experience of insult. 41.6% of the assaults were due to the effects of disease in assailants. However, no specific reason was found for physical menace and insult in most cases. 66.65%, 26.6% and 39.4% of the students reported physical assault, menace and insult to their tutors, respectively. CONCLUSIONS: Nursing students are subject to more violence because of young age and inadequate experience. Therefore, devising educational programs regarding occupational violence as well as its prevention and providing necessary support and consultation following violence are essential.